2001
DOI: 10.1002/qua.10022
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of acetonitrile with alkaline metal cations: A density functional, coupled‐cluster, and quadratic configuration interaction study

Abstract: ABSTRACT:A systematic quantum chemical study of CH 3 CN and its CH 3 CN· · ·M + 1:1 model adducts (M + ∈ {Li + , Na + }) is presented, with respect to binding energetics, structural and vibrational force field changes. Several gradient-corrected density functional levels of theory were employed (of both "pure" and "hybrid" character), together with the coupled cluster including double substitutions from the Hartree-Fock determinant (CCD) and quadratic configuration interaction including single and double subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 70 publications
3
13
0
Order By: Relevance
“…Another explanation is the lower polarizing power of Li + compared with the proton. Nevertheless, the covalent contribution to the bonding of neutral ligands with Li + is significant [31,32]. Quite interestingly, the lithium cation binds relatively strongly to aromatic systems [33][34][35][36][37][38][39][40] that are weakly polar or nonpolar, providing evidence that bonding mechanisms other than pure ion/dipole are acting.…”
Section: Introductionmentioning
confidence: 97%
“…Another explanation is the lower polarizing power of Li + compared with the proton. Nevertheless, the covalent contribution to the bonding of neutral ligands with Li + is significant [31,32]. Quite interestingly, the lithium cation binds relatively strongly to aromatic systems [33][34][35][36][37][38][39][40] that are weakly polar or nonpolar, providing evidence that bonding mechanisms other than pure ion/dipole are acting.…”
Section: Introductionmentioning
confidence: 97%
“…Studies of the solvation of alkali metal ions in acetonitrile solvents are not as common as studies of water systems, however good numbers of reports are available in literature [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Using mass spectrometry, Megyes et al [21] found up to six acetonitrile molecules surrounding the Li + ion in the gas phase.…”
Section: Introductionmentioning
confidence: 96%
“…The clusters of an alkali metal ion solvated with acetonitrile molecules have also been studied by many theoretical calculations in the past decades [30][31][32][33][34][35][36][37][38][39][40]. Various theoretical simulations have been made to describe the solvation of cations in acetonitrile molecules with, usually employing empirical/semi-empirical/realistic potential functions [30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations